2020
DOI: 10.1038/s41415-020-1534-6
|View full text |Cite|
|
Sign up to set email alerts
|

Dental core training: the trainee perspective

Abstract: Dental Core Training is a postgraduate training period, eligible following successful completion of foundation/vocational training, that has multiple entry points and endpoints with a varied duration from one to three years. The introduction of National Recruitment in 2017, away from a previous individual, Deanery-led process, has introduced new variables such as a ranking-system for preferencing training posts, with the outcome dependent on combined performance at interview and a situational judgement test fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Sir, you recently published an interesting research article regarding the career aspirations of female dental students and trainees. 1 It is well documented that there are increasing numbers of females entering the profession but this study further showed that more young female dentists are considering specialties that were traditionally male dominated. However, leadership positions are still disproportionately filled by males.…”
Section: Female Career Progressionmentioning
confidence: 57%
See 3 more Smart Citations
“…Sir, you recently published an interesting research article regarding the career aspirations of female dental students and trainees. 1 It is well documented that there are increasing numbers of females entering the profession but this study further showed that more young female dentists are considering specialties that were traditionally male dominated. However, leadership positions are still disproportionately filled by males.…”
Section: Female Career Progressionmentioning
confidence: 57%
“…With observance to current legislation, 1 photography can facilitate diagnosis, treatment planning and surgical procedures. 1,2 It is also useful both as a medicolegal tool and treatment goal conformational record. 3 Historically artists were used to produce illustrations from the descriptions of surgeons and physicians, which were highly influenced by their interpretation.…”
Section: Photos Pleasementioning
confidence: 99%
See 2 more Smart Citations
“…While recent research shows that nine-out-of-ten dental core trainees plan to undertake or have already undertaken an OMFS DCT post, the on-call component has been widely reported as the most challenging and daunting aspect of these posts, alongside lack of medical knowledge and ward duties. [2] , [3] , [4] , [5]…”
Section: Introductionmentioning
confidence: 99%